Rhizoctonia solani Kühn anastomosis group 3 as pathogen of potato and its sensitivity to seed-fungicides - Ivana Šafránková (Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis, 2004)
R. solani (Thanatephorus cucumeris (Frank) Donk) isolated from the sclerotia from the potatoes belongs to anastomose group 3 (AG 3), defined as the “potato type”. The present study shows the results of research into the efficiency of the seed-fungicides on R. solani (AG 3) isolates from various regions (12) of the Czech Republic. In addition to registered seed-fungicides we also tested the unregistered preparation Prestige 290 FS (pencycuron + imidacloprid). Our objective was to test the efficiency of the seed-fungicides on R. solani isolates and the sensitivity, or resistance, of the isolates to registered and unregistered seed-fungicides and/or to the active ingredients mancozeb, tolclofos-methyl, pencycuron and carboxin + thiram, and to the unregistered combination of the pencycuron + imidacloprid active ingeriens.